High impact projects of state structure plan of Negeri Sembilan2045–towards balanced and sustained economic growth - Kadar Hamsa, Abdul Azeez; Ibrahim, Mansor; Zen, Irina Safitri; Sulwani, Mirza; Ishak, Nurul Iman; Zakir, Muhammad Irham (IIUM Press, 2021)
This article is a review of Negeri Sembilan Draft State Structure Plan 2045. State structure plan sets the framework for the spatial planning and development to be translated in more detail in the next stage of development planning which is local plan. The review encompasses the goal, policies, thrusts and proposals to lead the development of Negeri Sembilan for the next 25 years. This review also highlights 9 high-impact projects proposed to be developed in Negeri Sembilan at the state level by 2045 through 30 policies and 107 strategies.